2015
DOI: 10.3126/jsan.v1i1.13587
|View full text |Cite
|
Sign up to set email alerts
|

Use of Granisetron for prevention of hypotension and bradycardia due to spinal anesthesia: A double blind randomised control trial

Abstract: of first publication with the work simultaneously licensed under a Creative Commons Attribution License that allows others to share the work with an acknowledgement of the work's authorship and initial publication in this journal. AbstractBackground: The common adverse effects of spinal anaesthesia include hypotension and bradycardia are due to sympathetic nerve blockade and activation of the Bezold-Jarisch reflex. The Bezold-Jarisch reflex in spinal anaesthesia may be mediated by peripheral 5-HT3 type seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…After SAB, heart rate trend showed non-significant difference between Group G and Group S throughout the study period. Our findings of change in heart rate were similar to Lamichhane et al [ 20 ], Mohammadi et al [ 17 ], and Shrestha et al [ 19 ] in two different studies; although they used higher doses of granisetron in their studies, they failed to observe significant heart rate variations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…After SAB, heart rate trend showed non-significant difference between Group G and Group S throughout the study period. Our findings of change in heart rate were similar to Lamichhane et al [ 20 ], Mohammadi et al [ 17 ], and Shrestha et al [ 19 ] in two different studies; although they used higher doses of granisetron in their studies, they failed to observe significant heart rate variations.…”
Section: Discussionsupporting
confidence: 90%
“…Saberi et al [21] observed that although the granisetron group showed a lesser decrease in systolic blood pressure as compared to normal saline, the difference was not statistically significant. Shrestha et al [19] also observed a similar non-significant difference in systolic blood pressure between the two groups. Both studies did not take surgical blood loss or other influencing factors into account and therefore the findings were different when compared to our study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The decrease in preload will stimulate the mechanoreceptor and chemoreceptor on the left ventricle wall, which is serotonin sensitive. [5, 10,11] Serotonin released by platelets, enterochromaffin cells, and the nervous system will bind to its receptor, specifically 5-HT3 type then activate the Bezold Jarisch Reflex (BJR). BJR is a cardioinhibitory mechanism with triad hypotension, bradycardia, and apnea.…”
Section: Introductionmentioning
confidence: 99%